2013
DOI: 10.4103/0972-124x.107478
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of anti-plaque efficacy of herbal and 0.2% chlorhexidine gluconate mouthwash in a 4-day plaque re-growth study

Abstract: Background:Chlorhexidine gluconate mouthwash has earned eponym of gold standard to treat and/or prevent periodontal disease. However, it has been reported to have local side-effects on long-term use. To explore a herbal alternative, the present study was carried out with an aim to compare the anti-plaque efficacy of a herbal mouthwash with 0.2% chlorhexidine gluconate mouthwash and normal saline.Materials and Methods:It was an examiner-blinded, parallel designed clinical trial, in which 90 pre-clinical dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 19 publications
5
42
0
5
Order By: Relevance
“…63 Aloe vera gel consists of 98 to 99% water and the remaining 1 to 2% of active compounds. The main active ingredients in aloe vera gel are aloin, aloeemodin, aloemannan, acemannan, aloeride, naftoquinones, methylchromones, flavonoids, saponin, sterols, amino acids, and vitamins.…”
Section: Aloe Vera Extractmentioning
confidence: 99%
“…63 Aloe vera gel consists of 98 to 99% water and the remaining 1 to 2% of active compounds. The main active ingredients in aloe vera gel are aloin, aloeemodin, aloemannan, acemannan, aloeride, naftoquinones, methylchromones, flavonoids, saponin, sterols, amino acids, and vitamins.…”
Section: Aloe Vera Extractmentioning
confidence: 99%
“…6,7 Chlorhexidine digluconate is considered the gold standard antimicrobial substance. 8 Nonetheless, the occurrence of adverse effects, such as dental staining and hypersensitivity reactions, has encouraged the search for new molecules. 8 The promising potential of natural substances against cariogenic microorganisms, and their application in the development of preventive and therapeutic products, has been explored in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…8 Nonetheless, the occurrence of adverse effects, such as dental staining and hypersensitivity reactions, has encouraged the search for new molecules. 8 The promising potential of natural substances against cariogenic microorganisms, and their application in the development of preventive and therapeutic products, has been explored in recent years. 9,10 There are already some commercially available formulations of mouthwashes and dentifrices containing natural substances.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, neem mouthwash is more preferable to 0.2% CHX gluconate mouthwash. 20 A study done by Krishnan et al 21 reported that there is an alteration in the oral hygiene habits and periodontal health and also the qualitative nature of the local bacterial biofilm is changed after the placement of an orthodontic appliance in a patient's mouth.…”
mentioning
confidence: 99%